The grassroots are always greener: Community-based organizations as innovators of shared solar energy in the United States. (August 2022) - Grimley, Matthew; Shastry, Vivek; Kânoğlu-Özkan, Dilge Güldehen; Blevins, Erica; Beck, Ariane L.; Chan, Gabriel; Rai, Varun
Abstract: Community-based organizations (CBOs) play important roles in the energy transition between niches, grassroots innovations, and established regimes. However, the motivations of CBOs to engage in energy transitions, and the functions they can perform within energy transitions, are under-studied. Using community shared solar (CSS) as a case study, we introduce theories of organizational innovation to explain why and how CBOs participate to shape energy transitions. We conduct two series of semi-structured interviews with CBOs: CBOs that have engaged in CSS projects in different ways across the United States and CBOs based in Texas that have not yet engaged in the energy transition but show the potential to engage in the future. We interpret the interviews by highlighting CBO pathways for "activation." We explain CBO activation with a framework of strategic, simple, and informal niches, in which CBOs can substitute for or complement top-down energy policies and normative energy-transition goals. We find that CBOs engage in the energy transition mainly through self-determined functions that generate many non-energy, organizational and societal benefits. By understanding these functions of CBOs, we highlight the need for further actions that, in supporting organizational innovation, can allow more CBO participation in the energy transition. Highlights: Community-based organizations (CBOs) are an understudied yet essential link for scaling energy transition innovations rapidly and equitably CBOs, such as churches, cooperatively owned utilities, and advocacy groups, operate in and outside of central energy transition social spaces Researchers and policymakers should consider targeting strategic, simple, and informal niches to promote CBOs' participation in the energy transition